Pengaruh Kepemimpinan dan Pemberian Insentif Kerja Terhadap Disiplin Kerja Pegawai Yayasan Nurul Huda Kuningan - Razak, Hafid; Sutanto, Aftoni (Program Studi Manajemen Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2024)
This study aimed to determine the extent of the influence of leadership and work incentives on employee discipline at the Nurul Huda Kertawangunan Foundation. Based on initial observations, the level of employee discipline at the foundation exhibited several issues, such as a high absenteeism rate (3.89%), tardiness, and non-compliance with dress code regulations, which are suspected to be influenced by leadership and work incentives. The research employed a descriptive and verification method, analyzing the collected data as it was and validating the research hypotheses. The sampling technique used was a saturated sample, consisting of 38 respondents. Data collection was conducted through questionnaires, interviews, and observations. Multiple linear regression was used as the analytical tool, with leadership and work incentives as the independent variables and work discipline as the dependent variable. The results indicated that leadership and work incentives both had a positive and significant effect on employee work discipline, both collectively and individually. This means that more effective leadership and higher work incentives lead to an increase in employee discipline at the Nurul Huda Kertawangunan Foundation. These findings imply that organizations seeking to improve employee discipline should focus on enhancing leadership effectiveness and providing sufficient work incentives